Manfaat Key Performance Indicators (Kpi) dan Balanced Scorecard Aplikasi pada Industri Media Penerbitan: A Literature Review - Hestari, Ema Tri; Prasetyoning Tyas, Ari Anggarani Winadi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The results of the literature review indicate that key performance indicators (KPIs) can be used to monitor employee performance relevant to the company's strategic goals. KPIs also help identify areas requiring attention and improvement. Additionally, the discussion emphasizes that KPIs need to be tailored to the needs of each industry. KPIs are used to ensure that every employee within the company works towards the same goals. The balanced scorecard (BSC) is used to integrate KPIs into a broader framework with four main perspectives: financial, customer, internal business processes, and learning and growth. The BSC provides a comprehensive view of the company's performance and helps identify and address issues the company may face. Keywords: Balanced Scorecard Applications, Key Performance Indicators (KPI), , Publishing Media Industry.